1979
DOI: 10.1029/ja084ia08p04267
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Pc 1–2 waves in the outer magnetosphere

Abstract: High time resolution measurements made inside the magnetopause from L = 7 to L = 14 by the University of California at Los Angeles fluxgate magnetometer aboard the Ogo 5 satellite demonstrate that Pc 1-2 magnetic field oscillations are occasionally present in portions of the outer magnetosphere. Eleven events have been studied so far, and all of them occurred in the afternoon sector at geomagnetic latitudes from 0 ø to +30 ø. Both the solar wind dynamic pressure and the magnetospheric cold plasma density were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…The unidirectional energy propagating away from the equatorial region was independent of event frequency or wave branch, suggesting that both the He+ and H+ wave branches do not undergo BWP propagation. Propagation away from the equator suggests that the EMIC waves were generated near the equator and propagated into higher magnetic field regions, consistent with earlier studies [e.g., Kaye and Kivelson , 1979; Fraser and Nguyen , 2001; Mursula et al , 2001].…”
Section: Discussionsupporting
confidence: 89%
“…The unidirectional energy propagating away from the equatorial region was independent of event frequency or wave branch, suggesting that both the He+ and H+ wave branches do not undergo BWP propagation. Propagation away from the equator suggests that the EMIC waves were generated near the equator and propagated into higher magnetic field regions, consistent with earlier studies [e.g., Kaye and Kivelson , 1979; Fraser and Nguyen , 2001; Mursula et al , 2001].…”
Section: Discussionsupporting
confidence: 89%
“…One study of data obtained beyond geostationary orbit supports the emphasis on low L generation. Using OGO 5 data, Kaye and Kivelson [ 1979] found that Pc 1-2 emissions were two to three times less common in the region L = 7-14 than at geosynchronous orbit, consistent with a primary source region inside L = 7. They also observed increased fluxes of low-energy (<100 eV) ions in association with their events which were attributed to encounters with detached plasma regions coincident with their events.…”
Section: Introductionmentioning
confidence: 82%
“…Since Pc 1-2 occurred for X = 0.1 -0.2 at geosynchronous orbit [Bossen et al, 1976], it was expected that events beyondL = 7 would occur below 0.1 Hz, assuming that X = 0.1 -0.2 held for the outer magnetosphere. It is interesting to note that in the 45 hours of data from local afternoon which were analyzed using the full temporal resolution of the OGO 5 magnetometer instorment (<0.144 s/sample), the occurrence of Pc 1-2 was 7% (derived from data presented by Kaye and Kivelson [ 1979]), suggesting that Pc 1-2 may have been underrepresented in the 4.6-s data. We conclude that the Kaye and Kivelson study did not examine sufficiently high frequencies.…”
Section: High L Dominancementioning
confidence: 99%
“…(ii) Boundary layer A number of workers have'discussed the generation of Pct-2 waves in or near the boundary layer regions:, KAYE and KIVELSON (1979) found 11 chiefly transverse mode LH wave events in the outer magnetosphere between L = 7.1-14.2 (average frequency = 0.11 Hz) which they attributed to ICW generation near the geomagnetic equator. There was also a strong connection with enhancements in the solar wind dynamic pressure.…”
Section: Generation and Propagation Of The Emissions (I) Cuspmentioning
confidence: 99%